A systematic review and meta-analysis of carfilzomib-associated thrombocytopenia as an adverse event in patients with multiple myeloma - Lara Smrdel; Igor Locatelli; Samo Zver; Martina Gobec (Therapeutic Advances in Hematology)
Background: Carfilzomib is a second-generation proteasome inhibitor (PI) used for combination therapy with dexamethasone and/or lenalidomide in patients with relapsed or refractory multiple myeloma. Reports indicate that PIs have a unique toxicity profile that includes thrombocytopenia as a hematologic adverse event; however, its occurrence has not yet been quantified systematically. Objectives: The main objective of our systematic review and meta-analysis is to investigate the incidence of thrombocytopenia in patients with multiple myeloma after treatment with carfilzomib. Design: Selection of studies and meta-analysis of trials was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Data sources and methods: Two investigators performed an independent literature search of PubMed, Web of Science, SciFinder, the Cochrane Central Register of Controlled Trials, as well as the US and EU clinical trials registries. The cumulative incidence and overall relative risk were calculated with the random effect model using RevMan and R statistical software. Results: The analysis included a total of 9237 patients, 2516 patients in single-arm studies and 6721 patients in randomized controlled trials (RCTs). A total of 47 studies were included; among these, 14 were RCTs. Analysis of currently available data showed that treatment with carfilzomib may increase the incidence of all-grade thrombocytopenia, and this correlated with the dose used. With supportive therapy alone, the incidence is 26%. The addition of carfilzomib to the treatment results in a 37% increase in incidence, whereas with bortezomib, the increase is slightly lower at 34%. Surprisingly, when treatment with carfilzomib and bortezomib was compared, bortezomib was found to be more likely to exacerbate high-grade thrombocytopenia (7%) than carfilzomib (3%). Conclusion: Clarification of these associations suggests that clinicians should be aware of the potential risk of high-grade thrombocytopenia occurring and monitor patients closely to take appropriate measures. Trial registration: Registered in PROSPERO under the number CRD42022314378.